The oral case presentation: towards a performance-based rhetorical model for teaching and learning - Chan, Mei Yuit (Taylor & Francis, 2015)
The oral case presentation is an important communicative activity in the teaching and assessment of students. Despite its importance, not much attention has been paid to providing support for teachers to teach this difficult task to medical students who are novices to this form of communication. As a formalized piece of talk that takes a regularized form and used for a specific communicative goal, the case presentation is regarded as a rhetorical activity and awareness of its rhetorical and linguistic characteristics should be given due consideration in teaching. This paper reviews practitioners’ and the limited research literature that relates to expectations of medical educators about what makes a good case presentation, and explains the rhetorical aspect of the activity. It is found there is currently a lack of a comprehensive model of the case presentation that projects the rhetorical and linguistic skills needed to produce and deliver a good presentation. Attempts to describe the structure of the case presentation have used predominantly opinion-based methodologies. In this paper, I argue for a performance-based model that would not only allow a description of the rhetorical structure of the oral case presentation, but also enable a systematic examination of the tacit genre knowledge that differentiates the expert from the novice. Such a model will be a useful resource for medical educators to provide more structured feedback and teaching support to medical students in learning this important genre.